The Role of Visual Rhetoric in the Vegetarian Movement: â€œMeet Your Meatâ€ Video of Animal Torture on the PETA Website - Desideria C. W. Murti (FISIP Universitas Atma Jaya Yogyakarta, 2012)
Abstract: Images have the power to create natural representation of reality, vividness in human memory and have rhetorical effect. However, visual rhetoric can create positive and negative feeling to persuade people. Negative feelings can be designed to make emotional reactions and spark action. Consequently, humans will consider ways to deal with the negative and discomfort feelings. In this paper, the writer analyzes the connection between visual rhetoric and emotional appeal by examining the controversial PETA video â€œMeet your Meatâ€. The writer will use the visual rhetoric, emotions, and cognitive dissonance theory to analyze the video and increase the understanding about the human emotions, especially disgust and guilt.Abstrak: Gambar memiliki kekuatan untuk menciptakan gambaran realitas yang alami, membuat kejelasan dalam ingatan manusia dan memiliki efek retoris. Namun, retorika visual dapat menciptakan perasaan positif dan negatif untuk membujuk orang. Perasaan negatif dapat dirancang untuk membuat reaksi emosional dan memicu tindakan. Akibatnya, manusia akan mempertimbangkan cara-cara untuk mengatasi perasaan-perasaan negatif dan ketidaknyamanan. Dalam tulisan ini, penulis akan menganalisis hubungan antara retorika visual dan daya tarik emosional dengan mengkaji video kontroversial PETA â€œMeet your Meatâ€. Penulis akan menggunakan teori retorika visual, emosi, dan disonansi kognitif untuk menganalisis video dan meningkatkan pemahaman tentang emosi manusia, terutama perasaan jijik dan rasa bersalah.